miR-27a rs895819 Polymorphism and Recurrent Pregnancy Loss in Caucasian Women: A Novel Genetic Risk Factor in a Challenging Fertility Dilemma - Georgia Panagou; Anastasios Potiris; Dimitra Dedousi; Despoina Mavrogianni; Ioanna Vassilaki; Athanasios Zikopoulos; Efthalia Moustakli; Antonios Sfakianakis; Nikolaos Kathopoulis; Angeliki Gerede; Periklis Panagopoulos; Ekaterini Domali; et al. (Current Issues in Molecular Biology)
Background: This case–control study investigates whether miR-27a rs895819 A>G polymorphism is associated with an increased risk of recurrent pregnancy loss (RPL) in Caucasian Greek women. Methods: This study included 93 women with at least two unexplained miscarriages before the 24th week of gestation (RPL group) and 107 women with no pregnancy loss history (control group). The miR-27a rs895819 A>G polymorphism was detected using PCR amplification, followed by DraIII-HF restriction enzyme digestion. Results: The GG genotype was linked to a significantly higher risk of RPL (p-value = 0.00005), whereas the AA genotype was associated with a significantly lower risk (p-value = 0.00036). The AG genotype appeared more frequently in women with RPL (49.5% vs. 44.9% in controls), but the difference was not statistically significant (p-value = 0.5139). Conclusions: To our knowledge, this is the first study demonstrating that the miR-27a A>G polymorphism was significantly associated with a higher risk of recurrent miscarriage in Caucasian women. These findings provide evidence that the GG genotype may serve as a potential genetic marker for identifying women at higher risk of recurrent miscarriage, offering valuable insights for genetic counseling and reproductive medicine.